Childhood trauma and its effect on adult relationships in It Ends with Us - Simatupang, Zefanya Aurora Magdalena; Thohiriyah, Thohiriyah (Pioneer: Journal of Language and Literature, 2025)
It Ends with Us by Colleen Hoover is a novel inspired by the author’s personal experience witnessing her mother endure domestic violence. The story follows Lily Bloom, a woman who grew up in an abusive household and later faces similar patterns in her adult romantic relationship. This study analyzes Lily’s psychological development using Anna Freud’s psychoanalytic theory, particularly focusing on defense mechanisms. The objective is to explore how Lily’s unresolved childhood trauma influences her thought processes and decision-making in adulthood. Through a qualitative method, the study examines narrative passages and character dialogues from the novel to identify psychological patterns. The analysis focuses on five of Anna Freud’s defense mechanisms: repression, denial, rationalization, displacement, and suppression, highlighting how Lily both consciously and unconsciously relies on these strategies to cope with trauma. The findings reveal that Lily’s exposure to domestic violence as a child profoundly impacts her adult emotional responses, making it difficult for her to confront abuse, assert boundaries, or think rationally in her relationship. Ultimately, the study emphasizes how defense mechanisms serve as psychological tools to shield individuals from the lasting effects of childhood trauma, as reflected in Lily’s behavior and emotional struggles throughout the novel.